Promoting Metacognitive Strategies in Teaching and Learning of Science - Dogra, Bharti (SCHOOL SCIENCE, 2025)
Metacognition is ‘thinking about thinking’. All those science teaching strategies which provide space to students to discuss, analyse, synthesise, paraphrase, summarise, apply, ask questions and think aloud, help in developing metacognition. Science students must be encouraged to record thinking process involved in reading science chapters, conducting laboratory activities, investigative projects as well as other science-based co-curricular activities. When science students revisit the recorded events or situations, this facilitates in understanding their own learning styles, needs, strengths and weaknesses which forms the basis of their understanding. Science teachers can also plan their strategies keeping in mind the needs of their students. This paper discusses various metacognitive strategies, such as concept-mapping, illustrations, brainstorming, planning strategies, and generating questions, evaluating actions, teaching capability, communication skills and journal keeping in science teaching-learning process.